2009
DOI: 10.1158/1940-6207.capr-08-0142
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diindolylmethane Enhances the Efficacy of Butyrate in Colon Cancer Prevention through Down-Regulation of Survivin

Abstract: Butyrate is an inhibitor of histone deacetylase (HDAC) and has been extensively evaluated as a chemoprevention agent for colon cancer. We recently showed that mutations in the adenomatous polyposis coli (APC) gene confer resistance to HDAC inhibitor-induced apoptosis in colon cancers. Here, we show that APC mutation rendered colon cancer cells resistant to butyrate-induced apoptosis due to the failure of butyrate to down-regulate survivin in these cells. Another cancer-preventive agent, 3,3′-diindolylmethane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 53 publications
1
52
1
Order By: Relevance
“…3,3Ј-Diindolylmethane (DIM) is an active metabolite of indole-3-carbinol present in cruciferous vegetables such as cabbage, broccoli, and kale (Grose and Bjeldanes, 1992). Previous studies have indicated that DIM has antiproliferative activity against various cancers (Hong et al, 2002a;Chen et al, 2006;Rahman et al, 2006;Kong et al, 2007;Bhatnagar et al, 2009). DIM has been shown to suppress cancer growth by inhibiting oncogenic molecules such as nuclear factor-B, Akt, and ␤-catenin in breast and prostate cancers (Chen et al, 2006;Rahman et al, 2006;Kong et al, 2007).…”
mentioning
confidence: 99%
“…3,3Ј-Diindolylmethane (DIM) is an active metabolite of indole-3-carbinol present in cruciferous vegetables such as cabbage, broccoli, and kale (Grose and Bjeldanes, 1992). Previous studies have indicated that DIM has antiproliferative activity against various cancers (Hong et al, 2002a;Chen et al, 2006;Rahman et al, 2006;Kong et al, 2007;Bhatnagar et al, 2009). DIM has been shown to suppress cancer growth by inhibiting oncogenic molecules such as nuclear factor-B, Akt, and ␤-catenin in breast and prostate cancers (Chen et al, 2006;Rahman et al, 2006;Kong et al, 2007).…”
mentioning
confidence: 99%
“…The diet with prebiotics decreased caecal pH which is the result of increased production of SCFA from carbohydrate fermentation. The treatment with prebiotics caused the highest increase in butyrate, a compound which has been demonstrated to have anti-tumour effects (Bhatnagar et al 2009). The diet with plant extract alone and in combination with prebiotics increased the caecal pH compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…CIAPs, X-chromosome linked inhibitor of apoptose protein (XIAP) and survival, (c): up-regulation of pro-apoptotic factors such as Bax gene, (d): liberation of mitochondrial cytochrome C in addition to stimulating of caspase-9 and caspase-3 [45] , and (e): inhibition of the NF-k B signaling pathway [46][47][48][49][50][51] . A vast number of diverse mechanisms of apoptosis induction by indoles have also been reported [52][53][54][55][56] . Figure 8 demonstrates the extrinsic and the intrinsic pathways of apoptosis (programmed cell death).…”
Section: Cell Death Induction By Indolesmentioning
confidence: 99%